2022
DOI: 10.1002/jbt.23227
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the effect of deer IGF‐1 on chondrocyte viability and IL‐1β‐induced inflammation response

Abstract: Clinical treatment of Osteoarthritis (OA) remains a challenge due to the poor self‐regeneration ability of cartilage. Deer antler is the only cartilage tissue that can completely regenerate each year. Insulin‐like growth factor 1 (IGF‐1) is one of the major active components in the deer antler that participate in regulating the rapid regeneration of deer antler cartilage. This has led us to speculate that deer IGF‐1 might potentially become a candidate drug for reducing damage and inflammation of OA. Thus, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Surprisingly, the only factor that correlated with cell proliferation individually was IGF-1, being the only molecule that did not depend on platelet concentration. This finding was in line with numerous studies in which IGF-1 stimulated cell proliferation in different cell types, such as retinal cells [ 23 ], neurons [ 24 ], chondrocytes [ 25 ], or tenocytes [ 26 ]. Therefore, although it seems reasonable to consider the importance of IGF-1 in PRP, no previous studies have demonstrated its dose-dependent effect on cell proliferation after PRP use in cell culture.…”
Section: Discussionsupporting
confidence: 90%
“…Surprisingly, the only factor that correlated with cell proliferation individually was IGF-1, being the only molecule that did not depend on platelet concentration. This finding was in line with numerous studies in which IGF-1 stimulated cell proliferation in different cell types, such as retinal cells [ 23 ], neurons [ 24 ], chondrocytes [ 25 ], or tenocytes [ 26 ]. Therefore, although it seems reasonable to consider the importance of IGF-1 in PRP, no previous studies have demonstrated its dose-dependent effect on cell proliferation after PRP use in cell culture.…”
Section: Discussionsupporting
confidence: 90%
“…A study conducted in an in vitro model of skin fibroblasts concluded that the higher the concentration of the extraplatelet factor IGF-1, the higher the proliferation at 96 h. IGF-1 was the only growth factor analyzed that was statistically significant when it came to proliferation [10]. This proliferative capacity has been found in different cell types such as chondrocytes, tenocytes, neurons and retinal cells [36][37][38][39].…”
Section: Extraplatelet Biomoleculesmentioning
confidence: 99%
“…As bladder cancer remains a common problem in regions where schistosomiasis is endemic, it is advisable to monitor individuals testing positive for schistosomiasis for prognostic indicators of bladder cancer [ 41 ]. The observed association between Schistosoma infection and infertility in both men and women may be explained by chronic inflammation, scar tissue formation, and severe granulomatous reactions [ 43 ]. In women, schistosomiasis can cause progressive fibrosis in the ovaries and fallopian tubes, leading to tubal occlusion and affecting the reproductive system [ 44 ].…”
Section: Intestinal and Urogenital Schistosomiasismentioning
confidence: 99%